Appraisal of e-governance as a mechanism for promoting efficiency in the Kwara State public service / Ashiru Olayemi - Olayemi, Ashiru (Universiti Teknologi MARA, Shah Alam, 2015)
Despite the undoubtful opportunities inherent in the adoption of e-governance initiatives in the world over, many government agencies are still reluctant in keying to this contemporary drive. This paper unravels (underscore) the significant impact of E-governance: (Information Communication Technologies ICT driven governance) on service delivery in the Kwara State Public Service. Both primary and secondary data were employed; secondary data were used to augment the primary data. The study adopted cluster sampling technique to select two ministries (two departments in each ministry) as a cluster. In all, forty questionnaires were returned out of fourth sixty questionnaires administered. The study affirms the contribution of ICT towards improving efficiency and effectiveness in government functioning, and the responsiveness of government to citizen's demand. The E-governance initiative has engendered transparency and accountability in the conduct of government business, as a result of improved interface between government and citizens via the internet. This paper therefore recommends that E-governance initiatives should be embraced by all publicly-owned institutions and agency because of its capacity to reduce the cost of governance, facilitate efficiency, effectiveness and timely delivery of services.